2023
DOI: 10.1088/1402-4896/accd9e
|View full text |Cite
|
Sign up to set email alerts
|

Controlling solar radiation forces with graphene in plasmonic metasurface

Abstract: Controlling and harvesting solar radiation pressure is a significant challenge, however, there are a few potential solutions, which are suitable for several key applications. In this study, an electrically tunable plasmonic metasurface is designed for the visible spectrum. Moreover, the normal and the tangential optical forces acting on the metasurface are calculated. Whilst presenting high efficiency in the anomalous reflection, the designed active metasurface provides tunability of optical forces acting on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…[ 17–21 ] A recent study has also demonstrated the potential to control and harness solar radiation pressure using active graphene in plasmonic metasurfaces. [ 22 ] Metasails can be seamlessly integrated into a single ultralight platform, minimizing the spacecraft's size, weight, and power (SWaP). The meticulous control of wavefront manipulation, facilitated by the metasurface, allows for precise management of the propulsion laser's reflection direction, achieving self‐stabilized beam‐riding.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17–21 ] A recent study has also demonstrated the potential to control and harness solar radiation pressure using active graphene in plasmonic metasurfaces. [ 22 ] Metasails can be seamlessly integrated into a single ultralight platform, minimizing the spacecraft's size, weight, and power (SWaP). The meticulous control of wavefront manipulation, facilitated by the metasurface, allows for precise management of the propulsion laser's reflection direction, achieving self‐stabilized beam‐riding.…”
Section: Introductionmentioning
confidence: 99%